Deletion of Salmonella enterica serovar Typhi tolC reduces bacterial adhesion and invasion toward host cells - Hussain, Ashraf; Ong, Eugene Boon Beng; Balaram, Prabha; Ismail, Asma; Kien, Phua Kia (Frontiers in Microbiology, 2023)
Background S. Typhi is a Gram-negative bacterium that causes typhoid fever in humans. Its virulence depends on the TolC outer membrane pump, which expels toxic compounds and antibiotics. However, the role of TolC in the host cell adhesion and invasion by S. Typhi is unclear. Objective We aimed to investigate how deleting the tolC affects the adhesion and invasion of HT-29 epithelial and THP-1 macrophage cells by S. Typhi in vitro. Methods We compared the adhesion and invasion rates of the wild-type and the tolC mutant strains of S. Typhi using in vitro adhesion and invasion assays. We also measured the expression levels of SPI-1 genes (invF, sipA, sipC, and sipD) using quantitative PCR. Results We found that the tolC mutant showed a significant reduction in adhesion and invasion compared to the wild-type strain in both cell types. We also observed that the expression of SPI-1 genes was downregulated in the tolC mutant. Discussion Our results suggest that TolC modulates the expression of SPI-1 genes and facilitates the adhesion and invasion of host cells by S. Typhi. Our study provides new insights into the molecular mechanisms of S. Typhi pathogenesis and antibiotic resistance. However, our study is limited by the use of in vitro models and does not reflect the complex interactions between S. Typhi and host cells in vivo.